ChemInform Abstract: N‐Heterocyclic Carbenes (NHCs) as Organocatalysts and Structural Components in Metal‐Free Polymer Synthesis. Issue 24 (23rd May 2013) - Fevre, Mareva; Pinaud, Julien; Gnanou, Yves; Vignolle, Joan; Taton, Daniel
Abstract Review: 261 refs.